A Case of Cardiac Metastasis from Uterine Cervical Carcinoma - Kazuhiro Okamoto; Tomoyuki Kusumoto; Noriko Seki; Keiichiro Nakamura; Yuji Hiramatsu (Hindawi Limited, 2015)
Cases of cardiac metastasis from uterine cervical carcinoma are rare. While they are occasionally found on autopsy, antemortem recognition is extremely rare. We confirmed a case of cardiac metastasis from cervical carcinoma antemortem, because we observed a decrease in platelet count during the course of treatment. The patient was a 27-year-old woman diagnosed with stage Ib1 uterine cervical carcinoma. Radical hysterectomy with pelvic lymphadenectomy was performed. Para-aortic lymph node metastasis was detected on positron emission tomography/computed tomography (PET-CT). Adjuvant chemotherapy was started, and most of the metastatic lesions disappeared. Pelvic lymph node recurrence was suspected on PET-CT during continued chemotherapy; therefore, treatment was shifted to radiation therapy. Tumor shrinkage was recognized, and the initial therapy was completed. A noticeable decrease in platelet count was recognized seven months after treatment. Multidetector CT was performed, and an intracardiac tumor was detected. The patient did not desire any further treatment. She died three weeks after the intracardiac tumor was confirmed. Few previous autopsy studies have reported cardiac metastasis from cervical carcinoma. Thus, it is necessary to consider the possibility of cardiac metastasis for patients diagnosed with terminal cervical carcinoma.